Desempenho fisiológico de sementes de algodão - Cocco, Deise Laura (2012)
The study aimed to evaluate the physiological potential of upland cotton seed lots (Gossypium hirsutum L.) by applying different vigor tests, in order to obtain information that might indicate the superiority of lots in the field. Six seed lots, cultivar FM 993, from different producers of Primavera do Leste MT, were evaluated from May to July 2012 by thousand seed weight test, water content, germination and vigor testing (first count, germination speed index, accelerated aging, electrical conductivity, emergence first count, emergence speed index and emergence). The trials were carried out in a completely randomized design with four replications. The electrical conductivity test, germination first count, germination and emergence speed index show efficiency in separating lots of cotton seed according to vigor levels.